Assessment of quality of life in the urban environment - Nikoofam, Mojdeh; Mobaraki, Abdollah (Horizon Research Publishing subscribe@hrpub.org, 2020)
Nowadays, the quality of life in urban environments is a controversial issue discussed in different studies as a response to many recent problems faced by cities around the world. This issue has been the center of discussion in different studies given that, based on tangible and intangible characteristics of human life. It has become one of the main concerns of every society. Since people carry out different responsibilities in urban environments, an assessment of city life is of major importance. Given that urban planning significantly impacts human health and the level of satisfaction, the study is aimed to assess the quality of life in the urban environments based on subjective and objective indicators that can be applied to improve health communication and urban vitality. For the purposes of this study, urban life in the city of Famagusta, as the most important city of North Cyprus, was investigated according to the quality of life indicator. © 2020 by authors, all rights reserved.
case study: Famagusta, N. Cyprus
Keywords: Objective Dimension; Quality of Life; Subjective Indicator; Urban Environment